Subverting exclusion : transpacific encounters with race, caste, and borders, 1885-1928 - Geiger, Andrea A. E. (Lamar series in western history., 2011)
Concerned with people called variously: eta, burakumin, buraku jumin, buraku people, outcastes, or "the lowest of the low", this book examines how their experience of caste/status-based discrimination in 19th century Japan affected their experience of race-based discrimination in the West of the US and Canada in the 19th and early 20th centuries